Coordination Compounds of the Polystyrene-Anchored Schiff Base Obtained From the Condensation of Chloromethylated Polystyrene, 3-Formylsalicylic Acid and o-Hydroxyphenylurea: Synthesis and Characterization of Polystyrene-Anchored Coordination Compounds (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Chloromethylated polystyrene (PS––CH2Cl) reacts with 3-formylsalicylic acid and forms polystyrene 3-formylsalicylate. The nucleophilic addition reaction followed by the elimination of one water molecule between polystyrene-3-formylsalicylate and o-hydroxyphenylurea in DMF in the presence of ethyl acetate results in the formation of polystyrene-anchored Schiff base, PSCH2––LH3 (19). The polystyrene-anchored coordination compounds of the types, [PSCH2––LH2Cu(OAc)(DMF)] (20), [PSCH2––LH2Cd(OAc)(DMF)] (21), [PSCH2––LH2Mn(OAc)(DMF)3] (22), [PSCH2––LH2FeCl2(DMF)2] (23) and [PSCH2––LH2MoO2(acac)] (24) (acacH = pentane-2,4-dione) have been synthesized by refluxing a DMF swollen suspension of 19 and appropriate metal saltscompound. The polystyrene-anchored coordination compounds have been characterized on the basis of elemental analyses, spectral (IR, reflactance, ESR) and magnetic susceptibility measurements. 19 behaves as a monobasic bidentate ON donor ligand in these coordination compounds. [PSCH2––LH2Cu(OAc)(DMF)] (20) is square-planar and paramagnetic, [PSCH2––LH2Cd(OAc)(DMF)] (21) is tetrahedral and diamagnetic. The paramagnetic compounds (22 and 23) and the diamagnetic compound (24) have attained an octahedral geometry.